Information Security Management in Financial Organisations: From Policy to Education and Training - Nalova, Endeley Margaret; Serkwem, Awiye Sharon (Advances in Social Sciences Research Journal, 2020)
The study set out to find out the extent to which analysing the cognitive competences of children, specifically executive function and visual perception, leads to the effective teaching of children with learning disability. An exploratory sequential mixed method research design was used and participants were selected purposively. A sample size of 10 pupils with learning disability was used. A diagnostic test and an observation checklist with items corresponding to the needs of the pupils was used to analyse pupils’ cognitive competences while a quasi-experiment was used to find out if teaching based on an analysis of competences was effective. Data were subjected to both descriptive and inferential statistics. Results showed that an analysis of cognitive competences has a significant influence on the effective teaching of reading and writing to children with learning disabilities. Recommendations were made.